Bioterrorism and the necessity of biodefense nowadays - Amasiadi, Natalia (Bioethica, 2021)
Introduction: Scientific progress has considerably increased the risk of unexpected bioterrorist attacks. In accordance comes the necessity for a potent “shield” of protection, known as “biosecurity” and widely referred as “biodefense”. However, ethical challenges and concerns, arising along with bioterrorism, are inevitable to address. Methods: COVID-19 outbreak immerged the significance of preexisting powerful biodefense systems. Primary factors to consider are theirs efficacy, the availability of capable emergency plans, adequate personal protective equipment, and sufficient funding. Least but not last comes the proper comprehension of risk assessment and the promotion of prevention, which contributes fundamentally in avoiding the outbreak, even before the harmful biological agent has begun spreading itself among the community. Results: Meticulous data recording will promote our knowledge of effectively constructive biodefense systems and will contribute in identifying crucial bioethical issues, as well to legislate accordingly, nationally, and internationally, in order to duly address the emerging threats. Conclusion: Drastic measures against bioterrorism are inevitable to take, so is the foundation of sufficient biodefense systems, which should lay on scientific knowledge that drives from relevant research, and general consent. Ultimately is, the establishment of international laws, to propel collaboration among nations and eliminate future bioterrorist attacks.